Changing trends in clinical characteristics and in-hospital mortality of patients with infective endocarditis over four decades - Diego Augusto Medeiros Santos; Rinaldo Focaccia Siciliano; Bruno Adler Maccagnan Pinheiro Besen; Tania Mara Varejão Strabelli; Caio Trevelin Sambo; Vitor de Medeiros Milczwski; Flora Goldemberg; Flavio Tarasoutchi; Marcelo Luiz Campos Vieira; Milena Ribeiro Paixão; Danielle Menosi Gualandro; Tarso Augusto Duenhas Accorsi; et al. (Elsevier, 2024)
Background: Infective endocarditis continues to be a significant concern and may be undergoing an epidemiological transition. Methods: Were studied 1804 consecutive episodes of infective endocarditis between 1978 and 2022. The mean age was 48 ( ± 19), and 1162 (64%) patients were male. Temporal trends in demographic data, comorbidities, predisposing conditions, microorganisms, complications and in-hospital death have been studied over the decades (1978-1988, 1989-1999, 2000-2010 and 2011-2022). The outcomes and clinical characteristics were modeled using nonlinear cubic spline functions. Findings: Valve surgery was performed in 50% of the patients and overall in-hospital mortality was 30%. From the first to the fourth decade studied, the average age of patients increased from 29 to 57 years (p < 0.001), with significant declines in the occurrence of rheumatic valvular heart disease (15% to 6%; p < 0.001) and streptococcal infections (46% to 33%; p < 0.001). Healthcare-associated infections have increased (9% to 21%; p < 0.001), as have prosthetic valve endocarditis (26% to 53%; p < 0.001), coagulase-negative staphylococcal infections (4% to 11%; p < 0.001), and related-complications (heart failure, embolic events, and perivalvular abscess; p < 0.001). These changes were associated with a decline in adjusted in-hospital mortality from 34% to 25% (p = 0.019). Interpretation: In the 44 years studied, there was an increase in the mean age of patients, healthcare-related, prosthetic valve, coagulase-negative staphylococci/MRSA infections, and related complications. Notably, these epidemiological changes were associated with a decline in the adjusted in-hospital mortality.